THE TEACHINGS OF WONG URIP KUDU URUP'S LIFE APPLICATION IN JAVANESE SOCIETY - Pujiyana, Pujiyana; Sawitri, Sawitri (Bajang Institute, 2025)
The teachings of human life that can be used for human life, one of which is wong urip kudu urup. Scientific article writing will reveal the teachings of life with urip kudu urup. The method used is descriptive qualitative with in-depth interviews, libraries, photo documents, videos, etc. The data obtained will be grouped to obtain valid ones so that the validity of the data will be obtained. Revealing the teachings of life from Urup that provide benefits for Javanese society. Wong Jawa should not be lost from Java, especially in the teachings of life that provide benefits to be useful in life. The review of the theory uses cultural theory, teachings of life and also Javanese society. In this teaching of life, urip and urup are useful for others, the knowledge that is owned is shared with others, the wealth that is obtained is realized not only ours, the importance of sharing, Health is an extraordinary pleasure, everything belongs only to the Almighty. Human life, no matter how high the degree, rank and wealth one has, still ends in death. Providing comfort and help to those in need.